Effect of Goat Manure and Moringa Leaf Extract on Vegetative Growth of Robusta Coffee (Coffea canephora) - Fitria Roviqowati; Muhammad Farhan Alfianto; Pardono Pardono; Edi Purwanto; Ahmad Yunus (Journal of Biodiversity and Biotechnology, 2024)
The use of organic fertilizers and growth stimulants in the form of natural PGR is the main solution to support sustainable coffee cultivation. This research aims to determine the best treatment combination, the best dose of goat manure, and the best concentration of moringa leaf extract for vegetative growth of robusta coffee TBM 1. The research was conducted in Kemuning Village, Ngargoyoso District, Karanganyar Regency in October 2023-April 2024. The method used was a Randomized Complete Group Design (RCBD) consisting of two factors and three replications. The first factor was goat manure (0, 3, 4, and 5 kg.plant-1) . The second factor was moringa leaf extract (0, 150, 200, and 250 g.L-1concentration). Data analysis used analysis of variance (ANOVA) at the 5% error level then continued with Duncan's Multiple Range Test (DMRT) at the 5% error level if there were significant results. The observed variables include plant height, stem diameter, number of leaves, number of branches, leaf area, and total chlorophyll. The results showed that the application of goat manure and moringa leaf extract affected the vegetative growth of robusta coffee plants. The combination of goat manure 4 kg.plant-1and moringa leaf extract at a concentration of 250 g.L-1had an effect on increasing chlorophyll b and total chlorophyll. Goat manure had no effect on all variables. Without the moringa leaf extract had better effect on plant height and the moringa leaf extract concentration of 250 g.L-1affected the increase in leaf area 6 weeks after application.